2014
DOI: 10.1002/lary.24607
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable thermoplastic mandibular advancement device for obstructive sleep apnea: Outcomes and practicability

Abstract: This is the first study in Asians demonstrating that an AT-MAD, if done properly, is a practical short-term treatment of OSA, with good outcomes including improved QOL. Its advantages are its low cost and ready-to-use nature. However, further randomized controlled trials are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
1
22
1
2
Order By: Relevance
“…In this case the device was inserted at a maximum protrusion of 60%, applying 0.5‐ to 1‐mm increments every 2 weeks. Banhiran et al found a significant reduction in AHI in 60.9% patients with AHI < 5 (of whom 75% presented moderate OSAHS). These authors used adjustable MADs and applied 0.5‐ to 1‐mm increments every 1 or 2 weeks for 4 to 6 months.…”
Section: Discussionmentioning
confidence: 96%
“…In this case the device was inserted at a maximum protrusion of 60%, applying 0.5‐ to 1‐mm increments every 2 weeks. Banhiran et al found a significant reduction in AHI in 60.9% patients with AHI < 5 (of whom 75% presented moderate OSAHS). These authors used adjustable MADs and applied 0.5‐ to 1‐mm increments every 1 or 2 weeks for 4 to 6 months.…”
Section: Discussionmentioning
confidence: 96%
“…For the purpose of comparison with previously published studies in patients with moderate‐to‐severe OSA, a complete response was defined as post‐treatment AHI < 5/hr, good response as post‐treatment AHI < 10/hr but > 5/hr, and treatment failure as ongoing AHI ≥10/hr. However, we were stricter and added ESS ≤10 to the concepts of complete and good response and ESS >10 to the concept of treatment failure.…”
Section: Methodsmentioning
confidence: 99%
“…They can be designed to monobloc or duobloc, depending on whether the MAD is composed of 1 or 2 pieces. [13,14] …”
Section: Introductionmentioning
confidence: 99%